Possible Role of Hidden Hyperthyroidism in Recurrent Supraventricular Tachycardia: Case Report and Brief Review - Rico Rudikan; Mochamad Faishal Riza (Jurnal Ners, 2026)
Supraventricular tachycardia (SVT) is a group of cardiac rhythm disorders characterized by a rapid heart rate, which may be regular or irregular. This condition arises from abnormal electrical activity originating above the His bundle, including the atrioventricular (AV) node and parts of the atria. Although SVT is generally not life-threatening, frequent, or prolonged episodes can significantly impact quality of life and increase the risk of complications. Hyperthyroidism is a well-known cause of various arrhythmias, including SVTs. Elevated thyroid hormone levels lead to overstimulation of adrenergic receptors and altered ion channel function, disrupting cardiac electrophysiological balance. In this report, we present a patient experiencing recurrent SVT episodes who was subsequently diagnosed with previously undetected hyperthyroidism. This case highlights the importance of comprehensive evaluation and maintaining high clinical suspicion to identify underlying conditions contributing to arrhythmias.